(untitled) (Palíndromo, 2025)
In the tradition of art history, the female body, depicted as an artistic nude, has been visually constructed as an object of contemplation and symbolically linked to ideals of beauty. This visual representation, shaped by a masculine and patriarchal perspective, has contributed to the construction and perpetuation of ways of seeing that associate women with specific categories of beauty, reinforcing the objectification of their bodies. This article analyzes, through a theoretical and critical approach to art history, how these visualities operate in the Western context and how they were subverted from the 1960s onward. To this end, it examines Vagina Painting (1965) by Shigeko Kubota and Interior Scroll (1975) by Carolee Schneemann. These artists challenged the canons of Western art by proposing a corporeal praxis that rejects the traditional conception of beauty associated with the female body. The analysis demonstrates that, from the 1960s onward, women artists restructured the relationship between art, body, and politics, using their own physicality as a means of resistance and subversion against the normative structures of Western art.